1998
DOI: 10.3109/17453679809117607
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin for prevention of heterotopic ossification after hip arthroplasty: A randomized comparison between 4 and 8 days of treatment

Abstract: In a randomized, parallel group study, we evaluated the efficacy of a 4-day versus an 8-day course of indomethacin (50 mg, 3 times per day), given as prophylaxis against heterotopic ossification after cementless total hip arthroplasty in 209 patients with arthrosis. Patients receiving the prophylaxis for 8 days had less (p = 0.03) severe heterotopic bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A role of PGE in clinically significant bone formation in the acute inflammatory phase following injury or surgery has been intimated by multiple studies. Inhibition of PGE production with the use of short‐term nonsteroidal anti‐inflammatory drugs has been shown to inhibit clinical bone formation 40–45. Inhibition of IL‐1β or other inflammatory cytokine‐mediated PGE production, as seen in this study, may account for this clinical finding.…”
Section: Discussionsupporting
confidence: 55%
“…A role of PGE in clinically significant bone formation in the acute inflammatory phase following injury or surgery has been intimated by multiple studies. Inhibition of PGE production with the use of short‐term nonsteroidal anti‐inflammatory drugs has been shown to inhibit clinical bone formation 40–45. Inhibition of IL‐1β or other inflammatory cytokine‐mediated PGE production, as seen in this study, may account for this clinical finding.…”
Section: Discussionsupporting
confidence: 55%
“…The minimum treatment period for NSAIDs appears to be 7 days (Neal et al 2000). Indomethacin used for 3 (van der Heide et al 1999) or 4 (Dorn et al 1998) days was found to show inferior results. Traditional non-steroidal anti-inflammatory drugs inhibit both cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2).…”
mentioning
confidence: 94%
“…10 Specifically in the treatment of fractures, time to healing and union rates are better in patients receiving ketorolac 3,20,34 than other nonsteroidal anti-inflammatory drugs (NSAIDs). 2,11,20 Our ketorolac analgesic regimen was well within the dosage and 1-week recommendation for NSAID administration. 13…”
mentioning
confidence: 71%